High prevalence of comorbidities and use of concomitant medication in treated people living with HIV in Germany – results of the BESIDE study. (February 2021) - Funke, B; Spinner, CD; Wolf, E; Heiken, H; Christensen, S; Stellbrink, HJ; Witte, V
Due to demographic changes in people living with HIV (PLHIV), physicians are challenged with age-related comorbidities and their management. In the absence of comprehensive data collection, the burden of comorbidities and co-medication in addition to antiretroviral therapy (ART) remains unclear for the German real-world setting. BESIDE was an observational, cross-sectional study evaluating the prevalence of comorbidities and use of co-medication in treated PLHIV. Regional distribution of study centers (n = 20), consecutive patient recruitment, and age-stratified sampling in alignment with national epidemiologic data aimed to ensure a representative sample (n = 453). The overall prevalence of comorbidities was 91.2%; 31.6% of patients had ≥4 comorbidities. The most common diagnoses were vitamin D deficiency (29.1%), depressive episode (27.8%), arterial hypertension (16.3%), and hypercholesterolemia (10.8%). 83.7% of patients were on co-medication; 21.2% taking ≥4 medications. The most common medications or supplements were vitamins (31.6%), anti-inflammatory agents (16.1%), renin–angiotensin system agents (12.1%), acid suppressants (11.7%), lipid modifying agents (10.8%); 1.3% of patients were on co-medication that should not be co-administered with ART, 41.5% on co-medication with potential for drug–drug interactions. The prevalence of comorbidities and use of co-medication among treated PLHIV in Germany is consistently high and increases across age groups, illustrating the complexity of HIV care involving appropriate ART selection.